Serological Survey and Molecular Detection of Infectious Bronchitis Virus in Broiler Chickens in Diyala Province, Iraq - Alazawy, Amer Khazaal Salih; Abdulhussain, Samer Raad; Nasser, Ammar Talib; Albaldawy, Amer Abdulameer Addas; Bande , Faruku; Jameel, Ghassan Hamdan (International Journal of Poultry Science, 2017)
Background and Objective: Infectious Bronchitis (IB) is considered one of the highly important contagious viral diseases of poultry worldwide. This study is carried out to determine the prevalence of IB in commercial broiler chickens in Diyala province, Iraq. Materials and Methods: The study was carried out during the period of August, 2014 until December, 2014. Swabs samples (n = 200) were collected from 20 flocks with a history of birds showing clinical signs suggestive of Infections Bronchitis Virus (IBV) infection. Samples were analyzed by immunochromatographic test and Reverse Transcription-polymerase Chain Reaction (RT-PCR). Results: About 77.5% (155/200) of the swabs samples were found seropositive for IBV infection. Whereas RT-PCR analysis using primers specific for the detection of IBV M gene showed that 67.5% (50/74) of the samples collected from 20 flocks were positive for IBV. Conclusion: It was concluded that the prevalence of IB is high among chickens commercially raised in the Diyala province of Iraq. Future molecular studies are needed to understand the genotype as well as the genetic diversity of IBV viruses found in the province to guide the choice of vaccines for prevention and control.